Compassion satisfaction and compassion fatigue in humanitarian aid workers: the relationship with shared trauma and coping mechanisms - Adwi, Mohamed; Abdellatif, Nada; Sadek, Ismail; Elsheikh, Mohamed (Frontiers in Psychology, 2025)
IntroductionForced displacement constitutes a global crisis impacting millions of people especially in the Middle East, leaving them impacted by traumatic history. Humanitarian aid workers (HAWs) who support displaced individuals are exposed to high risk of burnout and secondary traumatic stress (STS).MethodsThis study aimed to identify the prevalence of compassion satisfaction (CS) and compassion fatigue (CF), referring to burnout and STS, respectively, using the Professional Quality of Life Scale (ProQOL). The study explored the relationships between these factors and personal variables that are related to shared trauma, as well as coping mechanisms assessed using the Brief-COPE questionnaire among Middle Eastern HAWs working with displaced individuals.ResultsThe study involved 78 HAWs supporting displaced individuals in the Middle East. The mean age was 25.81 years (SD = ± 5.54); 55% were females, and the majority (88%) were Syrians. Approximately 90% of participants were engaged in Turkey and Syria. The most prevalent coping mechanisms were religion and planning. Being a graduate predicted burnout, whereas older age, previous mental diagnosis, and shared trauma predicted higher STS levels. Compassion satisfaction was predicted by active coping, and compassion fatigue was predicted by negative coping.ConclusionHAWs require education to recognize CF signs and psychological training to promote effective coping mechanisms, mitigate CF, and enhance higher levels of CS. More research is needed on the psychology of HAWs and the role of shared trauma and coping mechanisms.